GENERATION OF ANTIGEN-SPECIFIC REGULATORY T CELLS BYLACTOBACILLUS SPECIES. (22nd January 2022) - Weingarden, Alexa; Bousbaine, Djenet; Chen, Yiyin; Fischbach, Michael
Abstract: INTRODUCTION: There is a need for novel treatments for patients with inflammatory bowel disease (IBD) who do not respond to medical therapy. It is likely that IBD arises from dysfunctional interactions between the mucosal immune system and the gut microbiome, and manipulation of this interaction is therefore a promising therapeutic target. Signaling through the T cell receptor (TCR) may have a powerful role in controlling inflammation in IBD, as chimeric antigen receptor regulatory T cells (Tregs) which recognize colitis-associated antigens have been demonstrated to control inflammation in mouse models. We hypothesized that model antigen expression by two potential Treg-inducing organisms, Lactobacillus reuteri and L. plantarum, could stimulate antigen-specific Tregs which may be able to prevent colitis. Here, we demonstrate that expression of the ovalbumin-derived model peptides OT1 and OT2 by these species are recognized in vitro by transgenic CD8 and CD4 mouse T cells specific for OT1 and OT2, respectively. We also demonstrate that OT2 expression by L. reuteri can be recognized in vivo and generate antigen-specific Tregs. METHODS: We generated expression of OT1 and OT2 peptides in L. reuteri and L. plantarum in three subcellular locations: secreted, cell membrane-associated, and cell wall-associated. For in vitro assays, mouse dendritic cells (DCs) were pulsed with heat-killed cell pellets from each of these constructs or culture supernatant from secreted constructs, then incubated with either OT1 CD8 + or OT2 CD4 + T cells pre-stained with CellTrace Violet (CTV) for 3.5 days. For in vivo analyses, mice were gavaged with L. reuteri transformed with either empty vector or wall-associated OT2, or given ovalbumin in drinking water, followed by adoptive transfer of CTV-stained OT2 cells. OT2 cells were recovered from mesenteric lymph nodes (mLN) 7 days after adoptive transfer and stained for Foxp3. RESULTS: All OT2 constructs induced significant in vitro proliferation (decreased CTV staining) of OT2 cells compared to strains expressing empty vector, while secreted and membrane-associated OT1 constructs induced significant proliferation of OT1 cells. In vivo, L. reuteri expressing wall-associated OT2 induced significant OT2 proliferation in mLN compared to L. reuteri transformed with empty vector. A significantly higher proportion of these proliferated cells were Tregs (Foxp3 + ) compared to proliferated cells in mice treated with L. reuteri transformed with empty vector. CONCLUSION: These findings suggest that Lactobacillus species can generate antigen-specific proliferation of T cells in vitro, and that L. reuteri may be capable of inducing antigen-specific Tregs in vivo . Expression of antigens by this species may represent a method of generating tolerance in the intestine, which could lead to novel therapies for controlling inflammation in IBD.